COMPARATIVE PERFORMANCE OF CORPORATE SOCIAL RESPONSIBILITY OF ISLAMIC AND CONVENTIONAL BANKS IN INDONESIA PERIOD OF 2011-2015 - Fitri, Fauziah Aida; rahmawaty, rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this study is to compare the performance of Corporate Social Responsibility in Islamic and Conventional Banks in Indonesia period of 2011-2015 and to find out which of the banks stream perform better than the other. The performance is measured by the Global Reporting Initiative Index. The research used in this study is by calculating the scoring values of each index, and hypothesis testing. By using Content analysis method and Paired Sample T-test, 10 populations were selected that met the criteria, 5 Islamic and 5 Conventional Banks that revealed their social performance by using Economic, Environment, and Social Index. The data that is being used is secondary data obtained through annual reports from the official website of each Islamic and Conventional Banks.The results of this study indicate that there is a slightly significant difference of the comparison performance in Corporate Social Responsibility of Islamic and Conventional Banks in Indonesia period of 2011-2015. This phenomenon indicate that every year Islamic Banks in Indonesia working hard in order to develop their performance in term of Economic, Environment, and Social disclosure to be a serious competitor for Conventional Banks in the future of time. Thus, Conventional Banks leads to the Corporate Social Responsibility disclosure performance.